The influence of the 1968-1975 Congressional reforms on legislative policy-making - Moran, S; Moran, Susan J. (1986)
﻿ Congressional reform is the focus of my study. Congress (but primarily the House of Representatives) attempted to reform its workings from 1968 through 1975, so it might be more effective in developing comprehensive policies on national issues, and more independent of the executive branch. Reform raised expectations that the legislature would reassert its policy-making role, which had diminished during the preceding thirty years. My study examines the influence of these changes on the congressional decision-making process, including their impact on the important role played by external actors, interest groups and especially the President, who reacted to these changes. The study examines the process through an analysis of the development and passage of the most controversial provision, dealing with oil-price controls (Title IV), of Congress' major energy bill of 1975, the Energy Policy and Conservation Act (H.R. 7014). On 15 December 1975, Congress passed the Energy Policy and Conservation Act (EPCA) which President Gerald R. Ford signed into law on 22 December. The EPCA (Public Law 94-163) extended oil-price controls until 1979. The oilpricing provision had significant national and international economic and political implications. Merely to trace the tortuous chronicle of oil-pricing policy would be informative. But this study will go further by using this account to analyze congressional decision-making in the period immediately following Congress' attempts at reform. My study shows that although reforms eroded old norms and power centres, significantly altering some aspects of congressional decision-making (again primarily in the House), they did not create institutional mechanisms or distribute internal powers in such a way that Congress could independently initiate and develop comprehensive national policies. Congress remained more dependent on the President than many of its members understood. The final substance of the oil-pricing policy reflected the characteristic congressional decision-making process, which had become even more dispersed as it was democratized by reform. The committee system, without a strong executive or party control, divides issues in a way that limits decision-makers' options.